Quantification of facial morphology using 3D laser scanning method: preliminary results - Tahir, Zie Zie Azeanty; Setan, Halim; Suwardhi, Deni (2005)

(untitled)
The purpose of this study is to introduce 3-D laser scanning as a three-dimensional registration method for quantifying facial morphology and detecting changes in facial morphology during growth and development. By using 3D laser scanning method, three-dimensional co-ordinates for the bilateral landmarks Exocanthion and Cheilion and the midsagittal landmark Pronasale were determined in 20 subjects to ascertain the reproducibility of the method, and in 30 patients to detect changes in facial morphology due to growth and development. Linear and angular measurements were calculated by means of the 3-D co-ordinates in order to quantify facial morphology. During the observation period, significant changes in facial morphology were determined for the linear measurements. Advantages and disadvantages of current registration methods are discussed. It is concluded that 3-D laser scanning is suitable for 3-D registration method for quantifying and detecting development changes in facial morphology.